Characteristics, comorbidity burden and outcomes in centenarians undergoing surgery in a university hospital: A case series. (November 2021) - MacDowall, Jayden; Tully, Patrick; Guha, Ranj; Ferguson, Marissa; Tan, Chong; Weinberg, Laurence
Abstract: Introduction: As the population ages, so too does the age of those requiring surgery. People over the age of 100, centenarians, often have a greater degree of comorbidity and frailty than their younger counterparts but may also have a greater incidence of events requiring surgical intervention. There is, however, a dearth of literature describing the clinical course and practical considerations for this vulnerable population undergoing surgery. We aimed to describe the demographics of centenarians undergoing surgery, the procedures they receive, their intraoperative anaesthesia management, and their postoperative outcomes. Presentation of cases: A retrospective cohort study was completed to understand key perioperative and intraoperative variables linked to improved outcomes. Of the 25 patients included in this study, 22 (88%) were female and the median age was 101 years. Emergency cases predominated (72%) and 44% of surgeries occurred after hours. 60% underwent an intermediate risk surgery, and no centenarians underwent high risk surgery in this study period. Discussion: 64% of patients experienced at least one episode of intraoperative hypotension, with a median 3.5 epochs per patient. 68% of patients experienced postoperative complications and 20% of patients had a complication of Clavien-Dindo severity ≥ III. In centenarians, the risk of high severity postoperative complications was independent of the intrinsic procedural risk. Conclusion: Centenarian patients have an elevated burden of comorbidity, presenting often in the emergent setting. However, age alone should not preclude surgical intervention as expert multidisciplinary care can have acceptable outcomes. Highlights: Centenarian patients undergoing surgery are frail Most centenarian patients experience postoperative complications Surgery in centenarians can be feasible and undertaken safely Appropriate patient selection leads to acceptable outcomes Centenarians should not be denied surgery based on age alone